Effects of Manufacturing-induced Operating-conditions Amplified Stresses on Fatigue-life Prediction of Micro Gas Turbine Blades – A Simulation-based Study. Issue 1 (1st April 2022) - Fameso, Festus; Ramakokovhu, Unarine; Desai, Dawood; Salifu, Smith
Abstract: This study investigates the influence of residual stresses induced by the manufacturing process, on the fatigue life prediction of micro gas turbine blades manufactured by laser metal deposition additive manufacturing technique and heat-treated at different heat-treatment parameters. Finite element modelling, using commercial software Abaqus CAE ® and FE-Safe ®, was used to simulate the turbine blade and disk assembly's operations and analyze induced stresses, as well as estimate the life cycle of the assembly. Results show internal stress build-ups, up to 400 MPa in magnitude can be induced in engineered components right from the point of additive manufacture, the effects of which can become amplified to as much as double that scale or more by the time the component is in operation. As much as between 75% to 300% fatigue life prediction error reduction can hence be attained by simply accounting for induced stress contribution of the process of its manufacture, rendering cost-saving condition-based monitoring and maintenance/overhaul decision making options.